Enhanced thermal and mechanical properties by cost-effective carboxylated nanodiamonds in poly (vinyl alcohol). Issue 2 (3rd April 2018) - Zhang, Yuansai; Hua, Qingsong; Zhang, Jian Min; Zhao, Yuling; Yin, Hang; Dai, Zuoqiang; Zheng, Lili; Tang, Jie
Abstract: In this study, the high-energy ball-milled nanodiamonds (MNDs) are carefully treated with low-temperature annealing and mixed acids to obtain carboxylated MNDs (cMNDs). This process not only removes impurities but also grafts oxygen containing functional groups onto MNDs surfaces. Then poly (vinyl alcohol) (PVA)/cMND nanocomposites are prepared by a facile aqueous solution casting method. Compared with PVA/MND, an improved dispersion of nanoparticles in the matrix and higher nanoparticles content can be achieved by PVA/cMND. It is found that glass transition temperature ( T g ) and loss factor peak temperature ( T tanδ ) of PVA/cMND nanocomposites are both shifted to higher values than pure PVA. Thermal decomposition of PVA is obviously suppressed by cMNDs. The onset and maximum decomposition temperatures increases by over 17 °C and 24 °C, respectively. The thermal conductivity increases by 57.5%. Furthermore, tensile strength and Young's modulus of PVA are improved by 62.3% and 166.7% with the addition of cMNDs. Graphical Abstract: